2017
DOI: 10.1101/170258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maize leaf functional responses to drought episode and rewatering

Abstract: AbstractEffects of crop growth and physiological activity to drought and irrigation regimes have been extensively studied; however, the responses of plant growth, morphological and photosynthetic behaviors to drought episodes and thereafter rewatering receive a less attention. This field experiment was carried out directly in situ at an agricultural ecosystem research station during 2015-2016, in a northeastern China, on the renowned northeastern maiz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 103 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…The reduction in DM from short-term water stress at the beginning of the intensive vegetative growth stage was mainly caused by the reduction in plant height and leaf size and delay in leaf tip emergence (Çakir 2004). Some results from the same experiment showed that PD effects plant growth, leaf morphological traits and photosynthetic processes at vegetative and reproductive stages and leaf function traits of the plants experienced PD cannot fully restored compared to CK (Song et al 2018), which led to the decrease in the total biomass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in DM from short-term water stress at the beginning of the intensive vegetative growth stage was mainly caused by the reduction in plant height and leaf size and delay in leaf tip emergence (Çakir 2004). Some results from the same experiment showed that PD effects plant growth, leaf morphological traits and photosynthetic processes at vegetative and reproductive stages and leaf function traits of the plants experienced PD cannot fully restored compared to CK (Song et al 2018), which led to the decrease in the total biomass.…”
Section: Resultsmentioning
confidence: 99%
“…Weighing method was used to measure gravimetric soil water content (%) to a depth of 50 cm (every 6-8 days since early June in 2015 and early July in 2016 until the end of August). The detail of the method can be referred to Song et al (2018). We used soil relative extractable water (θ r , equation 1) to represent the soil available water conditions.…”
Section: Methodsmentioning
confidence: 99%